The time of the victims and hopes - Ballén-Molina, Rafael A. (Universidad Pedagógica y Tecnológica de Colombia, 2014)
In a country at war, like ours, we are all victims. That's the bad new. The good news is that the world is with us, pays tribute to our mortal victims and makes our surviving victims visible. Basque and Colombian citizens residing in the Basque Country / Euskal Herria, have made a fair recognition to the university professor, humanist and union leader, Jorge Adolfo Freytter Romero - assassinated by paramilitaries of the North Block of the United Self-Defense Forces of Colombia (AUC).